2023
DOI: 10.5944/ried.27.1.37491
|View full text |Cite
|
Sign up to set email alerts
|

Técnicas y aplicaciones del Machine Learning e Inteligencia Artificial en educación: una revisión sistemática

Wiston Forero-Corba,
Francisca Negre Bennasar

Abstract: El Machine Learning es un campo de la inteligencia artificial que está impactando últimamente en todas las áreas del conocimiento. Las áreas de las ciencias sociales, en especial la educación, no es ajena a ella, por tanto, se realiza una revisión sistemática de la literatura sobre aquellas técnicas y aplicaciones del Machine Learning e inteligencia artificial en Educación. La falta de conocimientos y habilidades de los educadores en Machine Learning e inteligencia artificial limita la implementación óptima de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Education has become one of the favourite application areas for AI researchers [4]. In their systematic review study on the use of AI in education, [5] identified its application for various purposes. These include the early detection of students' academic performance, predicting school dropout rates, improving student academic and career guidance, facilitating learning for students with disabilities, fostering the development of critical thinking, enhancing teachers' educational skills, and generating educational content.…”
Section: Introductionmentioning
confidence: 99%
“…Education has become one of the favourite application areas for AI researchers [4]. In their systematic review study on the use of AI in education, [5] identified its application for various purposes. These include the early detection of students' academic performance, predicting school dropout rates, improving student academic and career guidance, facilitating learning for students with disabilities, fostering the development of critical thinking, enhancing teachers' educational skills, and generating educational content.…”
Section: Introductionmentioning
confidence: 99%
“…AI tools can enhance innovative methodologies and continuous assessment, improving the effectiveness of educational institutions and supporting the continuous training of teachers. Thus, AI becomes a crucial ally in pedagogical renewal and the promotion of sustainable education (Forero-Corba & Negre Bennasar, 2024). Teacher training is a determining factor in educational quality, as well-trained teachers can transform the learning experience.…”
mentioning
confidence: 99%